An OpIE2 -DsRed marker disrupts female blood-feeding and shortens lifespan in the malaria vector Anopheles gambiae. - Sarig, Arad; Sar-Shalom, Evyatar; Kolley, Ebrima S M; Yonah, Elad Shmuel; Lamdan, Lee Benjamin; Lewin, Ariel Roselin; Partosh, Tamir; Pines, Gur; Bohbot, Jonathan D; Papathanos, Philippos Aris (Genetics, 2026)
Anopheles gambiae is one of the principal vectors of human malaria. Over the past 2 decades, transgenic mosquito strains have been essential tools for studying mosquito biology and developing genetic control strategies such as gene drives. Mosquito transformants are typically identified using fluorescent markers, which are assumed to be phenotypically neutral. While generating CRISPR-based gene drive strains carrying an OpIE2 -DsRed marker, we unexpectedly found that transgenic females were unable to blood-feed and were consequently sterile, whereas males initially appeared normal and fertile. Given the potential utility of dominant, female-specific sterility for mosquito control, we established additional strains controlling for transgene content and integration site, confirming that the OpIE2 -DsRed cassette caused the defect. Behavioral assays showed that females exhibited normal attraction to a membrane feeder but failed to initiate blood-feeding, performing repeated cycles of probing and proboscis grooming in rapid succession before ultimately leaving the feeder unfed. Microscopy showed that both sexes possessed a distally curved proboscis, providing a morphological explanation for the blood-feeding defect of females and the reduced male lifespan. A second promoter variant (OpIE2b), differing in flanking sequences at the IE-2 junction, drove strong marker expression without impairing blood-feeding or longevity. These findings demonstrate that minor differences in promoter architecture can produce major, unexpected phenotypic effects. OpIE2b provides a robust, phenotypically neutral marker for An. gambiae research, while OpIE2a highlights the need for rigorous validation of transgenic components intended for research and applied releases.